PENGARUH PRAKTIK INTERVENSI KESELAMATAN TERPADU TERHADAP PERILAKU KESELAMATAN PEKERJA: REPLIKASI MODEL - Sambudi Hamali; Teguh Sriwidadi; Asep Abdurrahman Tsani; Jeremy Rizky Marchziany; Yudhistira Dwi Hapsara (Pascasarjana Universitas Halu Oleo, 2019)
The purpose of this study was to determine the effect of management safety interventions, human safety interventions, technical safety interventions on safety behavior. The research method used is a quantitative method, with the type of causal research. Data collection is done by distributing questionnaires to all employees of 50 people. Data analysis method using SEM-PLS with WarpPLS 6.0 software. The results obtained from this study are management safety interventions affecting technical safety interventions, human safety interventions, and safety behaviors. Human safety interventions affect technical safety interventions and safety behavior. Technical safety interventions affect safety behavior. The results of this study indicate that to improve safety behavior, managers must improve management, human, and technical safety interventions. Keywords: management safety interventions, technical safety interventions, human safety interventions, safety behavior